LEXICAL SEMANTIC CHARACTERISTICS OF HYPONYMY IN ENGLISH- UZBEK LANGUAGES - Sabirova Nodira Karimboyevna; Duschanova Shohida Baxramovna (American Journals Publishing, 2024)
This article explores the lexical semantic characteristics of hyponymy in the context of the English and Uzbek languages. Hyponymy, a fundamental aspect of lexical semantics, plays a crucial role in understanding the hierarchical structure of word meanings within a language. By employing a comparative analysis, this study aims to highlight similarities and differences in hyponymic relations between English and Uzbek, shedding light on the intricacies of semantic structures in these languages.
Keywords: Lexical semantics, hyponymy, cross-linguistic analysis, English-Uzbek languages, semantic relationships.